The Effect of Partially Relevant Information on Inferential Localisation in Decision Dichotomies - Ceyhun Aksoy (Dilbilim Araştırmaları Dergisi, 1994)
A model was proposed for the utilisation of partially-relevant information in localising an inferential unit whose eigenvector selects a decision alternative in a dichotomy. It was hypothesised that (i) a decision D related to an input text would be affected by the partialy-relevant information given previously, (ii) the decision response for D would be faster in the presence of partially-relevant information than in its absence, (iii) in the presence of partially- relevant information, the decision response for D would be faster than that for its counterpart D\ (iv) the partially-relevant information and D would interact on response time. The subjects were presented a tape-recorded text with positive, negative, or no partially-relevant information prior to the input text, after which a question was asked to elicit the decision response. Response time was measured and recorded together with the response. The results supported hypotheses (i), (ii), and (iv). Implications regarding the model were discussed, and possible areas of its applicability were indicated.